Answer:
x = 0
y =
![-(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rl8evc58egdmlf26tw2nmq4e4e1zwx7ma0.png)
Explanation:
Given the two equations:
7x - 2y = 1
2y = x - 1
We need to find the value of x and y.
First, let's make x the subject of the 2nd equation:
2y = x - 1
x = 2y + 1
Now, we substitute this into the first equation and solve for y:
7x - 2y = 1
7(2y + 1) - 2y = 1
14y + 7 - 2y = 1
12y = -6
y = -6/12 = -1/2
Now, putting the value of y into 2nd equation, we can solve for x:
x = 2y + 1
x = 2(-1/2) + 1
x = 0
Thus, the value of x and y are:
x = 0
y =
![-(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rl8evc58egdmlf26tw2nmq4e4e1zwx7ma0.png)